Development and Validation of a Novel Five-Dye Short Tandem Repeat Panel for Forensic Identification of 11 Species - Cui, Wei; Jin, Xiaoye; Guo, Yuxin; Chen, Chong; Zhang, Wenqing; Wang, Yijie; Lan, Jiangwei; Zhu, Bofeng (Frontiers in Genetics, 2020)
Species identification of unknown biological samples is of fundamental importance for forensic applications, especially in crime detection, poaching and illegal trade of endangered animals as well as meat fraud. In this study, a novel panel was developed that can simultaneously identify 10 different animal species (Gallus gallus domesticus, Anas platyrhynchos domesticus, Ovis aries, Sus scrofa domesticus, Bos taurus, Equus caballus, Columba livia domestica, Rattus norvegicus, Mus musculus, Canis lupus familiaris) and human beings by amplifying 22 short tandem repeat (STR) loci in a multiplex PCR using a set of five fluorescently labeled dyes. This novel 22-STR panel was validated by optimization of PCR conditions as well as sensitivity, reproducibility, precision, species specificity, DNA mixture, and tissue/organ consistency. The results of developmental validation showed that the 22 STR loci achieved high species specificity among 10 animal species and human beings, and the sensitivity of this panel was 0.09 ng. This 22-STR panel identified different meat in mixed samples, and the minimum detected mixture ratio in the current test was 10% (0.1 ng/1 ng). This sensitive, accurate, and specific 22-STR panel can be used for forensic species identification and the detection of meat fraud and adulteration.